The Application of Heptamethine Cyanine Dye DZ-1 and Indocyanine Green for Imaging and Targeting in Xenograft Models of Hepatocellular Carcinoma - Zhang, Caiqin (Int J Mol Sci, 2017)
Near infrared fluorescence (NIRF) imaging has strong potential for widespread use in noninvasive tumor imaging. Indocyanine green (ICG) is the only Food and Drug Administration (FDA) -approved NIRF dye for clinical diagnosis; however, it is unstable and poorly targets tumors. DZ-1 is a novel heptamethine cyanine NIRF dye, suitable for imaging and tumor targeting. Here, we compared the fluorescence intensity and metabolism of DZ-1 and ICG. Additionally, we assayed their specificities and abilities to target tumor cells, using cultured hepatocellular carcinoma (HCC) cell lines, a nude mouse subcutaneous xenograft model of liver cancer, and a rabbit orthotopic transplantation model. We found that DZ-1 accumulates in tumor tissue and specifically recognizes HCC in subcutaneous and orthotopic models. The NIRF intensity of DZ-1 was one order of magnitude stronger than that of ICG, and DZ-1 showed excellent intraoperative tumor targeting in the rabbit model. Importantly, ICG accumulated at tumor sites, as well as in the liver and kidney. Furthermore, DZ-1 analog-gemcitabine conjugate (NIRG) exhibited similar tumor-specific targeting and imaging properties, including inhibition of tumor growth, in HCC patient-derived xenograft (PDX) mice. DZ-1 and NIRG demonstrated superior tumor-targeting specificity, compared to ICG. We show that DZ-1 is an effective molecular probe for specific imaging, targeting, and therapy in HCC.